Oscillation Theorems of Solutions of Third Order Nonlinear Neutral Differential Equations with Periodic Coefficients - M. AbdAlameer, Nidhal; Haitham Qasem, Intisar; Ali Mohamad, Hussain (Al-Nahrain Journal of Science, 2026)
In this article, nonlinear neutral equations of the 3rd order with several periodic coefficients and forcing terms are studied, where some conditions are found that include the existence of only oscillatory solutions for this type of equation. All cases in which non-oscillatory solutions are likely to exist were discussed and appropriate conditions were found to exclude these cases. Some illustrative examples of the extracted results are added.